Anatomic study of septocutaneous system of the human fetuses’ lower leg: posterior tibial artery - Stevanovic, Goran; Daković-Bjelaković, Marija Z.; Djordjević, Boban; Paravina, Jadranka M.; Golubović, Ivan Z.; Janković, Irena D.; Radojković, Milan D.; Nestorović, Milica D.; Ignjatović, Nebojša S.; Krstić, Miljan S. (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Lower-leg septocutaneous system of perforating blood vessels represents the vascular basis of fasciocutaneous flaps. Additionally, it is of a particular importance when designing distally based fasciocutaneous flaps which represent the “workhorse” in the reconstruction of the distal third of the lower leg and foot. The aim of this study was to analyse the vascular anatomy of posterior tibial artery and its septocutaneous (fasciocutaneous) perforating arterial vessels. Methods. The dissection was conducted on 20 fetuses of both sexes and of gestational age from 20 to 28 weeks. Cluster analysis was applied to the data on vascular anatomy of posterior tibial artery and its septocutaneous performating arterial vessels. Results. A total of 212 perforating arterial vessels was identified. The average number of perforating arterial vessels was 5.32 (ranging from 4 to 7). It was identified that septocutaneous perforating blood vessels are more likely to be found at certain levels (“safe levels of finding perforators”). These are: second, third, fifth and sixth tenth (measured as a distance from intermalleolar line to popliteal crease). Conclusion. The presence of septocutaneous system of perforating blood vessels and reliability of their localization even in the fetal period allows application of these findings in the lower leg reconstructions in children of early age. It also contributes to the greater level of understanding of anatomy of the lower-leg vascular system. Finally, it provides a basis for understanding the development of this system as it is now possible to compare results obtained on fetuses with those obtained on adults.
Keywords: anatomy; fetus; leg; surgical flaps; tibial arteries